The Effect Of Economic Conditions On Electricity Consumption In Malaysia - Nur Athirah Najwa Azhar; Noor ‘Adilah Ibrahim; Shahrina Ismail (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.